Estructura de la comunidad de peces en la costa oriental de la isla de Cabagua, Venezuela - Parra, Berta (2003)
The community structure of fishes on a sandy beach with patch of Thalassia and coral reefs was studied at Punta Las Cabeceras, Cubagua Island, Venezuela. Diurnal monthly samples were obtained from March 1999 to February 2000. Numerical abundance of fish species was recorded to determine the specific diversity. A total of 1 268 individual from 38 species and 20 families were identified: Haemulidae, Scaridae and Gerreidae were the more abundant, with 7, 4 and 3 species, respectively. Nicholsina usta, Eucinostomus argenteus, Halichoeres bivittatus and Tylosurus crocodiles made up 74.38% of the abundance, and present in 50% of the samples. The number of species occasional visitors was 30 (78.94%), indicative of the mobilization from another areas. On a monthly basis, the species number varied between 2 and 12; diversity index between 0.98 and 2.93 bits ind-1., equitability (J´) from 0.44 to 0.98, both indices showing the same tendency. N. usta and E. argenteus had the highest biological index equivalent to 59.1 and 60.0 %, respectably, of the maximum possible total and were dominants and characteristics fishes of the community.